Analisis Nilai Moral Novel Bulan Jingga dalam Kepala Karya M Fadjroel Rachman - Sri Murti; Siti Maryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The objectives of the study were to describe the moral values ​​associated with human relationships with God, the relationship with oneself, relationships with others, and the human relationships with the environment contained in the novel of Bulan Jingga di Atas Kepala M. Fadjroel Rachman. Technique of collecting data using literature study technique and record. Based on the results of research and discussion of novel Bulan Jingga diAtas Kepala of M. Fadjroel Rachman can be deduced that the moral value in human relations with his Lord found 28 citations, the moral value of relationship with self found 20 citations, the moral value of human relationships with fellow found 13 citations, the moral value of the relationship with the environment found 7 citations. So it can beconcluded that in the novel of the Bulan Jingga di Atas Kepala of M. Fadjroel Rachman contained moral values ​​relating to human relationships with God, the relationship with self, relationships with others, and human relationships with the environmentthat proved to be true. Keywords: Analysis, Moral Values, Novels